A survey of tobacco dependence treatment guidelines in 121 countries - Piné-Abata, Hembadoon (Blackwell Publishing Ltd, 2013)
AIMS: To report progress among Parties to the World Health Organization (WHO) Framework Convention on Tobacco Control (FCTC) in developing national tobacco treatment guidelines in accordance with FCTC Article 14 guideline recommendations. DESIGN: Cross-sectional study. SETTING: Electronic survey from December 2011 to August 2012; participants were asked to complete either an online or attached Microsoft Word questionnaire. PARTICIPANTS: One hundred and sixty-three of the 173 Parties to the FCTC at the time of our survey. MEASUREMENTS: The 51-item questionnaire contained 30 items specifically on guidelines. Questions covered the areas of guidelines writing process, content, key recommendations and other characteristics. FINDINGS: One hundred and twenty-one countries (73%) responded. Fifty-three countries (44%) had guidelines, ranging from 75% among high-income countries to 11% among low-income countries. Nearly all guidelines recommended brief advice (93%), intensive specialist support (93%) and medications (96%), while 66% recommended quitlines. Fifty-seven percent had a dissemination strategy, 76% stated funding source and 68% had professional endorsement. CONCLUSION: Fewer than half of the Parties to the WHO FCTC have developed national tobacco treatment guidelines, but, where guidelines exist, they broadly follow FCTC Article 14 guideline recommendations.